ON THE BINARY NATURE OF PLEIONE - Menchenkova, E. V.; Luthardt, R. (Одеські астрономічні публікації, 2017)
From analysis of radial velocity measurements the binary nature of Pleione is discussed. A possible orbital period of about 35 yr was detected.